Trunk accelerations and rotations during anterior cruciate ligament injury: An illustrative case study - Williams, J. H.; Rizzuto, S.; Jaskowak, D.; Eaton, R. (Sport Performance & Science Reports, 2019)
Unfortunately, anterior cruciate ligament (ACL) injuriesare all too common in competitive sports (Agel et al.,2016). Further, it is estimated that female athletes are 2-10fold more likely to suffer an ACL tear than their male counterparts (Hewett et al., 2009). Hewett and colleagues (Hewettet al., 2009; Hewett & Meyer, 2011) have implicated coronalor frontal plane trunk movement as an important ACL injury mechanism. As the trunk rotates laterally in relation to thestance limb, the center of mass force vector moves laterally.This can result in a greater lever arm relative to the kneeand an increased potential for knee abduction (Hewett et al.,2009; Hewett & Meyer 2011). Video analyses confirm thatstopping, landing and cutting, is associated with lateral trunk lean as well as lateral rotation (twisting). This typically results in valgus collapse and subsequent injury to the ipsilateral knee (Boden et al., 2000; Hewett et al., 2009; Sheehan et al.,2012). Unfortunately, the use of video limits detailed quantitative analysis of trunk movements during an ACL injury. However, with the advent of wearable technologies, movement speeds, trunk accelerations and trunk rotational velocities can be measured via GPS, accelerometer and gyroscope devices.